2021
DOI: 10.1111/evo.14291
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence for a positive relationship between hybridization and diversification across seed plant families

Abstract: Hybridization has experimental and observational ties to evolutionary processes and outcomes such as adaptation, speciation, and radiation. Although it has been hypothesized that hybridization and diversification are positively correlated, this idea remains largely untested empirically, and hybridization can also potentially reduce diversity. Here, we use a hybridization database on 170 seed plant families, life history information, and a time‐calibrated phylogeny to test for phylogenetically‐corrected associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 120 publications
(279 reference statements)
0
18
0
Order By: Relevance
“… 2005 ), or by producing new hybrid species (Mallet 2007 ). This creative role for hybridization may explain observed correlations between hybridization frequency and net species diversification, as seen in salamanders and plants (Mitchell and Whitney 2021 ; Patton et al. 2020 ).…”
mentioning
confidence: 94%
“… 2005 ), or by producing new hybrid species (Mallet 2007 ). This creative role for hybridization may explain observed correlations between hybridization frequency and net species diversification, as seen in salamanders and plants (Mitchell and Whitney 2021 ; Patton et al. 2020 ).…”
mentioning
confidence: 94%
“…Is the propensity to hybridize itself an adaptive life history strategy? Our discussions here build on previous considerations of these questions (e.g., Grant 1971;Ellstrand et al 1996;Whitney et al 2010;Folk et al 2018a;Mitchell et al 2019;Mitchell and Whitney 2021). The prevalence of reticulation has also led some to question whether a bifurcating tree is the most appropriate way to model the diversification process and conceptualize evolutionary history more generally (e.g., Funk 1981;Linder and Rieseberg 2004;Bapteste et al 2013).…”
Section: Introductionmentioning
confidence: 89%
“…In fact, even in cases of tight pollinator specialization, such as figs, hybridization can still occur, perhaps in particular during pollinator-host switches (Wang et al 2021). A study by Mitchell et al (2021) examined the correlation of 11 different traits with hybridization and found weak positive associations between perenniality, woodiness, outcrossing, abiotic pollination, and larger genomes and increased frequencies of hybridization, but some of these results were scale dependent. Hybridization is a complex phenomenon that appears to require the confluence of several to multiple abiotic and biotic factors (and for populations to persist once formed), and so it is not surprising that particular traits generally show inconsistent relationships with hybridization frequency.…”
Section: Trait and Phylogenetic Correlations With Hybridization Frequ...mentioning
confidence: 99%
“…Hybridization is another key field in evolutionary biology, with a major question being the extent to which hybridization and/or introgression between taxa act as evolutionary fuel in promoting speciation, evolution, and diversification (Anderson and Stebbins 1954; Barrett and Schluter 2008;Stelkens et al 2014;Marques et al 2019;Taylor and Larson 2019) versus the circumstances under which these processes act as homogenizers, reducing diversity or leading to extinction (Rhymer and Simberloff 1996;Wolf et al 2001;Todesco et al 2016). At the macroevolutionary scale, hybridization has been linked to evolutionary radiation (Anderson and Stebbins 1954;Stebbins 1959;Barton 2001;Seehausen 2004;Yakimowski and Rieseberg 2014;Berner and Salzburger 2015;Stankowski and Streisfeld 2015;Grant and Grant 2019;Marques et al 2019;Meier et al 2019) and potentially diversification (Mitchell and Whitney 2021). Hybridization can also lead to adaptation (Lewontin and Birch 1966;Campbell and Snow 2007;Hovick et al 2012;Stankowski and Streisfeld 2015;Mitchell et al 2019) and speciation (Rieseberg 2003;Rieseberg et al 2007;Soltis and Soltis 2009;Abbott et al 2013).…”
mentioning
confidence: 99%
“…2019; Meier et al. 2019) and potentially diversification (Mitchell and Whitney 2021). Hybridization can also lead to adaptation (Lewontin and Birch 1966; Campbell and Snow 2007; Hovick et al.…”
mentioning
confidence: 99%